Systematization of “Induction: Strategic Learning” for VERITAS University students by the Counseling Office during a pandemic by the virus responsible for COVID-19 - Bulgarelli Bolaños, Raquel María Bulgarelli Bolaños (Innovaciones Educativas, 2022)
This systematization details the didactic experience “Induction: Strategic Learning” through emergency remote teaching, which was planned, coordinated, and executed by the Guidance Office of VERITAS University amid the educational changes generated by the virus responsible for COVID-19, in order to promote adaptability to the career, especially regarding the changes in educational paradigms, the objective of the systematization is to evaluate the lessons learned from this experience to strengthen the University’s work of supporting new students. The techniques of this systematization were observation, survey, and interview, and its sources were the student population that participated in the induction and four teachers who accompanied their students to the induction conducted by the Counseling Office. In conclusion, the students were satisfied with the induction, were informed about the guidance service, and learned about academic self-regulation and adaptability to educational transitions; the Counseling Office and the teachers learned about the usefulness of applying inductions within the class schedule at this level and the frequency in the application of study habits of their students. Finally, it is recommended that the Counseling Office continue to apply this induction in the first week of the term by coordinating directly with the faculty.